Penerapan Nilai-Nilai Profil Pelajar Pancasila Dalam Kegiatan Pengenalan Lapangan Persekolahan Di SD Kanisius Wonogiri - Astika, Selly (STABN RADEN WIJAYA WONOGIRI JAWA TENGAH, 2022)
The Pancasila student profile is part of the vision and mission of the Ministry of Education and Culture, which is very important to implement in educational institutions to develop students into Pancasila students who demonstrate faith, devotion to God Almighty and the values ​​of noble morality, critical reasoning, global diversity, mutual cooperation. cooperative, independent and creative. It is hoped that the Pancasila student profile can be implemented well as part of the independent learning curriculum, it is hoped that it will be applied both in learning and in the independent learning program in introductory activities to the school field. The aim of this research is to describe the profile values ​​of Pancasila students through a series of school field introduction (PLP) activities in 2023. This research is a type of descriptive qualitative research. Data was collected through documentary research and interview methods. The informants were 3 PLP students at Kanisius Wonogiri Elementary School, Central Java. Data were analyzed using a process of data reduction, presentation and drawing conclusions. The results of the research show that the value of the Pancasila student profile is realized through mutual cooperation actions, literacy and numeracy activities, religious teaching, camp exercises and school culture. The profile of Pancasila students is very important and is related to the Indonesian government's efforts to implement character education in schools and higher education.